الرقمنة كمدخل لتحسين الخدمة العمومية في الجزائر قطاع العدالة نموذجًا - لمقـدم, عبد الغنـي (جامعة الوادي -University eloued, 2017)
يعتبر دخول الرقمنة كتقنية حديثة من أهم الإستراتيجيات المنتهجة لتحسين الخدمة العمومية،باعتبارها نقلة نوعية، من إدارة تقليدية تعتمد على الأرشيف الورقي، إلى إدارة حديثة تعتمد على تكنولوجيا حديثة وإمكانيات مادية وبشرية متطورة،تتماشى والتحولات والتطورات العالمية السريعة،حيث سرعة تدفق المعلومات وتحسين خدمة المواطن،وبالتالي تناولت الدراسة في شقها النظري مفهوم وخصائص الخدمة العمومية،أنواعها وخصائصها،وكذا مفهوم وخصائص الرقمنة،أشكالها ونماذجها،ثم التعرف على دور الرقمنة في تحسين الخدمة العمومية،والدوافع التي أدت إلى تطبيقها ،إما تماشيًا مع التطورات السريعة العالمية،أو ظروف فرضتها عوامل داخلية وخارجية،إلا أنها تطبيقها يمر بعدة مراحل ويخضع لمتطلبات مالية وإدارية وتقنية وأمنية وبشرية،لتحقيق الأهداف المرجوة،من خلال النتائج المحققة بعد كل المعوقات والتحديات التي تواجه عملية تطبيق الرقمنة على الخدمة العمومية،والتي تحول دون تحقيق الأهداف التي أنشأت من أجله، وتنعكس هذه الصورة على التجربة الجزائرية على غرار العديد من الدول الأخرى لتطوير وتحسين أداء الخدمة بقطاع العدالة عبر كل الهياكل القضائية التابعة له على مستوى إقليم الدولة،حيث أن المتتبع للتطور التاريخي،التي مر به قطاع العدالة في الجزائر،من الأحادية إلى التعددية،أي من أحادية النظام القضائي إلى ازدواجية النظام القضائي، يدرك ان هناك نية التغيير نحو الأفضل قبل ظهور الرقمنة كتقنية حديثة في هذه المجال،ومع التسارع التكنولوجي السريع في كثير من المجالات الاقتصادية والاجتماعية والثقافية وحتى الامنية،وفي إطار مواصلة سلسلة الإصلاحات من طرف الحكومة الجزائرية،لتبني الرقمنة لتطوير قطاع العدالة كإستراتيجية تضمنها برنامج الحكومة،حيث حققت الجزائر العديد The introduction of digitization as a modern technology is one of the most important strategies to improve the public service, as a qualitative leap from a traditional management based on paper archives to a modern management based on modern technology and advanced human and material capabilities. This is in line with rapid global changes and developments. The study examined the concept and characteristics of public service, its types and characteristics, as well as the concept and characteristics of digitization, its forms and models, and then the role of digitization in improving the public service, Its characteristics and characteristics, as well as the concept and characteristics of digitization, its forms and models, and then the role of digitization in improving the public service and the motives that led to its application either in line with the rapid global developments or circumstances dictated by internal and external factors. Administrative, technical, security and human resources, to achieve the desired goals, through the results achieved after all the obstacles and challenges facing the application of digitization on the public service, And this image is reflected in the Algerian experience, like many other countries, to develop and improve the functioning of the justice sector across all its judicial structures at the level of the country's territory, as it follows the historical development undergone by the justice sector In Algeria, from unilateralism to pluralism, from a single judicial system to a double judicial system, , Aware that there is an intention to change for the better before the emergence of digitization as a modern technology in this field, and with the rapid technological acceleration in many economic, social, cultural and even security fields, and as part of the series of reforms by the Algerian government to adopt digitization to develop the justice sector as a strategy included in the government program , Where Algeria has achieved many achievements at the level of this sector, , The Ministry is seeking to disseminate it to all its branches in order to enhance the citizen's confidence and ease its burdens. There are future programs on the government agenda that are still in the framework of the study, and thus Algeria has achieved tremendous progress in adopting digitization to improve public service in the justice sector
ماستر سياسة عامة
Keywords: الرقمنة ، الخدمة العمومية ، الإدارة التقليدية ، الإدارة الحديثة ، وزارة العدل, traditional Management , Moderne Management, Ministry of justice : public service , Digitization